A brief review: application of recycled polyethylene terephthalate as a modifier for asphalt binder - Ben Zair, Mohamed Meftah; Mohd Jakarni, Fauzan; Muniandy, Ratnasamy; Hassim, Salihudin; Ansari, Anwaar Hazoor (Springer, Cham, 2022)
The management of the waste materials produced on the earth is one of the highly substantial environmental issues. Hence, the increasing usage of plastic every year is one of the concerns across the entirety of the world. The limiting landfill conditions and higher production of the waste plastic materials stress the researcher to manage it alternatively. Conversely, the growing number of heavy vehicles on roads cause road distress to asphalt pavements that contain pure asphalt binders that are insufficiently resistant. Civil engineers and scientists have attempted to address such issues by enhancing the performance of asphalt pavement via modification of asphalt binders’ properties. This paper summarized the possible utilization of waste polyethene terephthalate (PET) for binder modification. It has been evaluated that the PET can significantly improve the binder properties. The chemical modified PET showed better performance in term of physical and rheological properties. In addition, the compatibility of PET with binder has been highlighted with modified chemical structures and via morphological assessment of modified binder. In addition to solving landfilling issues of waste PET plastic, such recycling approaches generated in these studies can also be used by asphalt researchers to explore future avenues of improvement for the characterization of asphalt binder as a paving material.